C-type natriuretic peptide and collagen X marker are aberrant in skeletal dysplasias - Carroll, Ricki S; Olney, Robert C; Duker, Angela L; Coghlan, Ryan F; Schelhaas, Andrea J; Mackenzie, William G; Ditro, Colleen P; Brown, Cassondra J; O’Connell, David A; Horton, William A; Johnstone, Brian; Espiner, Eric A; et al. (Journal of bone and mineral research, 2025)
Skeletal dysplasias (SD) are rare genetic disorders affecting skeletal development and bone growth. Whereas specific gene mutations have been identified in many, however, the molecular signaling pathways contributing to the phenotype are poorly understood. The C-type natriuretic peptide (CNP) signaling pathway is a driver of normal endochondral bone growth and underlies the impact of several genetic disorders of bone growth, including achondroplasia, the most common form of SD. In this cross-sectional study of 73 children with SD, comprising 7 distinct forms, we have examined the association of plasma concentrations of bioactive CNP and bio-inactive NTproCNP (recognized bio markers driving growth) and of collagen X marker (CXM) (an established biomarker of the growth plate response) with age and with annualized height velocity (HV). Although significant associations were identified with age in several disorders, the association of NTproCNP and of CXM with HV was aberrant except in type II collagen disorders and MOPD II. In OI, CNP and NTproCNP were reduced in proportion to severity of OI phenotype. Reduction in CNP exceeded NTproCNP, suggesting that higher rate of clearance/degradation of bioactive CNP occurs in OI. Across a wide range of HV in subjects with OI, biomarkers were dissociated and unrelated to HV. Similar changes were observed in 3 other forms of SD (multiple epiphyseal dysplasia, microcephalic osteodysplastic primordial dwarfism type II, and Morquio A syndrome). Although limited numbers of affected individuals within each group were studied employing a single sample at one time point, the results indicate aberrant responses both within biomarkers and when related to HV. Importantly, we identify enhanced rates of CNP clearance in OI and other forms of SD, which suggests CNP agonists could have therapeutic benefits.